Antiproliferative potential of carbon monoxide - Ye. G. Starikova (Бюллетень сибирской медицины)
The investigation results showed carbon monoxide had antiproliferate potential in Jurkat cells. This gaseous transmitter led to delay of G1 phase of cell cycle. Inhibition of p38 MAPK-dependent pathways didn’t influence on CO-mediated proliferation of Jurkat cells changes.